Internet addiction and its relationship to psychosocial adjustment among schooled adolescents. - A field study in some secondary schools in M'sila city - ghadbane, amina; ammour, amar (Journal of Social Sciences and Humanities, 2023)
The study aimed to find out the relationship between the internet addiction and psychological social adjustment among schooled adolescents. It also detection on the level of each variable in this study .It was based on the use of the descriptive approach where the data were collected by relying on two scales prepared for this purpose after verifying their validity and reliability, and they were applied to the study sample, which was estimated at 357 male and female schooled adolescents were randomly selected to participate, from some secondary schools in M'sila city. The study results revealed the following: • The level of Internet addiction among the study sample is average. • The level of psychological and social adjustment among the sample members is average. • There are statistically related relationship between the internet addiction and the psychosocial adjustment.